Chitosan hydrogel inclusion in fish mince based emulsion sausages: Effect of gel interaction on functional and physicochemical qualities - Chattopadhyay, Kasturi; Xavier, K.A. Martin; Layana, Porayil; Balange, Amjad Khansaheb; Nayak, Binaya Bhusan (International journal of biological macromolecules, 2019)
Chitosan has been reported to possess diverse applications in food industry. The cross linking properties of chitosan beneficially affects the protein-carbohydrate interactions which in turn enhances the functional properties in emulsion based meat products. In this context, the current study was conducted to incorporate hydrogel with different concentrations of chitosan (0%, 0.125%, 0.25%, 0.375% and 0.5%) into fish mince (Pangasianodon hypophthalmus) sausages in order to develop a functional sausage products with appealing flavour and desirable texture. The comparative analysis of various functional properties of the produced sausages showed that inclusion of chitosan gel had significant effect (p < 0.05) on the emulsion stability, gel-strength, pH, cooking yield, WHC, structural-compactness, texture, colour and sensory attributes of the products when compared with control. Further, from the study, it can be inferred that, sausages with 0.25% chitosan content (CS-2) uphold the best necessary functional and physiochemical attributes and presumed to be a superior ready-to eat product. •The effect of chitosan gel inclusion in pre-emulsified fish mince was studied.•Emulsion stability was improved with all combinations of chitosan gel addition.•Improved water holding capacity, colour and textural parameters observed•Better sensory score attributing to the consumer's preference of chitosan incorporated fish sausages.